PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea Mays Saccharata Sturt) PADA PEMBERIAN BIOCHAR SEKAM PADI DAN PUPUK NPK - Islami, Muh Farhan Ansa; Rauf, Abdul; Nursalam, Nursalam (Fakultas Pertanian, Universitas Tadulako, 2024)
The objective of this study was to investigate the response of sweet corn growth and yield to the application of rice husk biochar and NPK fertilizer, and to determine the optimal combination of biochar and NPK dosages that enhance sweet corn growth and yield. The study was conducted in Makmur Village, Palolo Subdistrict, Sigi District, Central Sulawesi, Indonesia from January to April 2022. A two-factorial randomized block design (RBD), namely biochar dosage and NPK fertilizer dosage, was employed. Each factor had three levels, and each treatment combination was replicated three times. The results showed that the interaction between NPK fertilizer and rice husk biochar was significant only for ear length and ear weight, regardless of ear type (tasselled or untasselled). The application of rice husk biochar significantly reduced the need for NPK fertilizer in sweet corn cultivation.